상전이 및 점 결함에 의한 Fe1-xCoxSe2 합금의 열전특성 향상 - 박현진; 김준수; 김세준; 서원선; 김현식; 김상일 (대한금속·재료학회지, 62(12), 2024)
This study investigates the thermoelectric properties of Fe1-xCoxSe2 (x = 0, 0.25, 0.5, 0.75, and1) alloys using theoretical modeling approaches. The Single Parabolic Band (SPB) model was employed tocalculate band parameters such as density-of-states effective mass (md*), non-degenerate mobility (μ0),weighted mobility (μw), and B-factor. As the alloying content (x) increased, the B-factor improved, leadingto higher predicted maximum zT values. For CoSe2 (x = 1), optimizing the carrier concentration to ~1.3 ×1019 cm-3 can potentially enhance zT to ~0.64, a 21-fold increase over the experimental value (~0.03). TheCallaway-von Baeyer (CvB) model was used to analyze thermal transport properties, revealing that theincreased x strengthens phonon scattering by point defects, resulting in a continuous decrease in latticethermal conductivity (κl). Specifically, a phase transition from orthorhombic to cubic structure occurs asx increases, with a mixed phase observed at x = 0.75 and a complete transition to cubic at x = 1. Thisstructural change significantly impacts both electronic and phonon band structures, leading to a dramaticincrease in the B-factor and a substantial reduction in κl for x > 0.75. These findings suggest that CoSe2alloying, coupled with the induced phase transition, can significantly improve the thermoelectricperformance of FeSe2-CoSe2 alloys. KCI Citation Count: 0